Proposal for a classification of posts in primary dentition review of the literature - Mezarina Mendoza, Jhon Paul Iakov (2022)
Dental caries in children is a non-contagious multifactorial disease that causes demineralization of hard dental tissues and can provoke irreversibly damage the dental pulp. When this happens, we are faced with 2 treatment routes, the pulpotomy and the pulpectomy; the latter consists of the removal of the cameral pulp and the root canals. After the pulpectomy, the tooth can be reinforced with the placement of dental posts, mainly in the anterior sector, because there is no classification or organization of the types of dental posts used in pediatric dentistry. The objective of this study is to present a proposal for the classification, or organization of dental posts used in primary dentition, based on the classifications of dental posts in adults. For this, a bibliographic search was carried out in the databases: PUBMED, MEDLINE, EBSCO, LILACS in English, Portuguese and Spanish, without restriction of the years of publication. We conclude that there is no classification or organization of posts, spikes or pins used in pediatric dentistry in the literature, therefore we present a classification proposal for academic and clinical purposes.